KESETIAAN SUAMI ISTRI DALAM MANAWA DHARMASASTRA - Dewa Gede Kusuma Tirta (UHN IGB Sugriwa Denpasar, 2022)
Most people at first from the courtship to the marriage level usually pay less attention to the causes and effects that will arise in the household, they consider it normal, only based on consensual feelings and sometimes only based on sexual desire. The function of marriage or wiwaha is an effort to realize the life goals of Grhasta Dormitory. A faithful relationship should last until death, in short it is made as the highest law by husband and wife. In the Manawa Dharmasastra literature, it is explained that marriage is a sacred act (sacrament, samskara), which is an engagement between two parties who fulfill God's commands and suggestions, so that family life and neighboring relatives run well in accordance with Hindu religious teachings. However, nowadays there are still many divorce cases and the cases are increasing every year between the text and the context being discontinuous. If it is handled wisely and wisely through serious and continuous application, especially referring to the values ​​of loyalty, then husband and wife will succeed in improving the quality of their lives in building relationships for the creation of a harmonious family (Hita Graha)). Based on the background above, the writer is interested in raising the title of the research on Faithfulness of Husband and Wife in Manawa Dharmasastra.